Non-suturing microvascular anastomosis in maxillofacial reconstruction- a comparative study. Issue 6 (June 2020) - Mudigonda, Surya kiran; Murugan, Senthil; Velavan, K.; Thulasiraman, Selvakumar; Krishna Kumar Raja, V.B.
Abstract: Aim: The aim of the study is to compare the advantages and disadvantages of non-suturing anastomotic methods over conventional microsuturing for microvascular venous anastomosis. Materials and methods: All patients reporting to the institute for hard and soft tissue reconstruction (Primary/secondary) were enrolled in the study. Patients with systemic comorbidities, peripheral vascular diseases, or anatomical aberration of the indicated donor site were excluded from the study. The patients selected for the study were randomly allocated to five groups of different techniques of venous anastomosis, namely Group I (conventional microsuturing), II (fibrin sealant reinforced microsuturing), III (couplers), IV (staplers), V (Laser Assisted Vascular Anastomosis (LAVA)). Intraoperative anastomotic time, flap ischaemic time, patency and leakage were the parameters that were assessed for all five groups. Results: 80 Patients were randomly allocated to five groups and each group comprised 16 patients. The mean ischaemic time and standard deviation of Group I and Group II were 256.19 ± 10.622 min and 255.19 ± 11.083 min, and for groups III, IV, and V were 193.38 ± 9.972 min, 139.06 ± 6.413 min, and 139.31 ± 6.364 min respectively (p < 0.001). Mean anastomotic time and standard deviation were 19.813 ± 1.5366 min in Group I and 20.281 ± 1.6514 min in Group II. The non-sutured anastomosis groups III, IV, and V showed a mean anastomotic time of 5.375 ± 0.9876 min, 4.175 ± 0.7664 min, and 3.856 ± 0.867 min respectively (p value < 0.001). In Groups I and II, 18.8% of patients had delayed patency and in Groups III, IV and V, immediate patency was observed in all subjects (p value 0.030). In Groups I and II, 18.8% and 6.3 % of patients respectively had leakage, whereas all patients in Groups III, IV, V had no leakage from the anastomotic site (p value 0.119). Conclusion: Based on the results of the study, non-suturing techniques should be preferred over microsuturing technique whenever appropriate for venous anastomosis.